Pertanggungjawaban Pelaku Usaha Terhadap Keracunan Makanan Pada Konsumen - Michael Jose Rizal; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Fakultas Hukum Universitas Warmadewa, 2024)
Consumer protection regarding expired food circulating in the community is very important. Therefore, consumers need to be careful in choosing products so as not to suffer losses and maintain the health of their bodies. How is the legal protection of consumers related to expired food circulating in the community? How is the responsibility of business actors for the distribution of expired food based on the Consumer Protection Law? Normative legal research method is used to answer this question. Protection of consumers related to expired packaged food is carried out by business actors, government, non-governmental organizations, and consumers through various efforts. The responsibility for products traded by business actors and circulated to the market or consumers is the responsibility of business actors who distribute these products.